Fault-tolerant control for fuzzy switched singular systems with persistent dwell-time subject to actuator fault - Shen, Hao; Xing, Mengping; Wu, Zheng-Guang; Park, Ju H. (Fuzzy sets and systems, 2020)
This paper investigates the problem of fault-tolerant state feedback fuzzy control for discrete-time nonlinear switched singular systems subject to the actuator fault. The typical Takagi-Sugeno model is utilized to process the nonlinearity of the systems. For the purpose of describing the intermittent occurrence of fast and slow switching among subsystems, a switching signal complying with persistent dwell-time switching regularity is introduced for the first time into the analysis of nonlinear switched singular systems. The primary objective is focused on constructing a fault-tolerant controller which can ensure that the closed-loop system is exponentially admissible with a prescribed l2 -gain performance in the presence of actuator fault. By using mode-dependent Lyapunov function and employing an improved matrix decoupling method, sufficient conditions with less conservatism for the existence of the desired controller are established and the explicit form of the controller gains is presented. For explaining the effectiveness of the proposed method, two illustrative examples are given finally.